PROTOTYPE SISTEM PENCARIAN REKOMENDASI LOKASI KERAJINAN LOKAL DI YOGYAKARTA MENGGUNAKAN TRAVELING SALESMAN PROBLEM (TSP) DENGAN ALGORITMA GENETIKA - Handy Eka Putra Anwar; Deviani Titi Nautami; Dhina Puspasari Wijaya (Teknoin, 2016)
Local craft industry is now starting to compete with other industries in the process of advancing the region and even the country's economy. Yogyakarta, as a tourism destination known for its traditional cultural values would be more interesting if the culture of local crafts can be more openly introduced. The high interest in the local craft makes tourists want to see, and even to try the process of making of local crafts in Yogyakarta. Traveling Salesman Problem (TSP) with genetic algorithm method works by providing Yogyakarta's local craft location recommendation, from closest to farthest location that can be visited by tourists with the use of Global Positioning System (GPS) on their smartphones. Traveling Salesman Problem (TSP) with genetic algorithm (GA) method provides the best traveling route for tourists who want to find and visit Yogyakarta's local craft location in one hand.